2020
DOI: 10.1186/s40249-020-00780-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating level of interleukin-6 and CD8+ T cell exhaustion are associated with progression of COVID-19

Abstract: Background Coronavirus disease 2019 (COVID-19) is pandemic. It is critical to identify COVID-19 patients who are most likely to develop a severe disease. This study was designed to determine the clinical and epidemiological features of COVID-19 patients associated with the development of pneumonia and factors associated with disease progression. Methods Seventy consecutive patients with etiologically confirmed COVID-19 admitted to PLA General Hospital in Beijing, China from December 27, 2019 to March 12, 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…57 This exhaustion of T-cell lymphocytes was associated with the progression and severe manifestation of COVID-19. 58,59 Limitations Firstly, only a limited number of our included studies reported on CD4 cell counts, viral loads and ART -a fact that is likely to have impacted the precision of the meta-regression analysis of this study. Indeed, most studies focussed on the characteristics of COVID-19 patients rather than its effects on PLWH.…”
Section: Discussionmentioning
confidence: 99%
“…57 This exhaustion of T-cell lymphocytes was associated with the progression and severe manifestation of COVID-19. 58,59 Limitations Firstly, only a limited number of our included studies reported on CD4 cell counts, viral loads and ART -a fact that is likely to have impacted the precision of the meta-regression analysis of this study. Indeed, most studies focussed on the characteristics of COVID-19 patients rather than its effects on PLWH.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous prospective study, we have demonstrated that lower circulating counts of T lymphocytes, CD4 + T cells, and CD8 + T cells as well as higher circulating levels of neutrophil proportion, neutrophil/lymphocyte ratio, interleukin-6, CRP, and procalcitonin facilitate the progression of COVID-19. Of those, CD8 + T cell exhaustion plays an important role in the pathogenesis of COVID-19 [18]. Other studies have also shown that disease severity is negatively associated with NK cells and CD3 + , CD4 + , and CD8 + T lymphocyte levels, while intensive expansion of highly cytotoxic effector T cell subsets, such as CD4 + effector-granulysin, CD8 + effector-granulysin, and NKT CD160, is associated with convalescence of COVID-19 patients [19-21].…”
Section: Discussionmentioning
confidence: 99%
“…In the early HIV-era hydroxyurea, was used in the treatment of HIV and demonstrated synergistic effects with e.g nucleoside reverse transcriptase inhibitors [ 187 , 188 ]. Based upon its cytoreductive, anti-inflammatory and antithrombotic capabilities, it may be a highly efficacious agent in the treatment of COVID-19 patients with leukocytosis and imminent ARDS due to a rising potentially life-threatening cytokine storm [ [184] , [185] , [186] , [187] , [188] , [189] ]. In this context, the hydroxyurea-specific myeloid targets - monocytes and macrophages – may be of particular importance.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…As in HIV-infection, hydroxyurea may also in COVID-19 attenuate viral rebound by decreasing CD4 T cell proliferation, as well as preventing the exhaustion of CD8 T cells(for Reviews: 187,188). Indeed, the cytostatic effect of hydroxyurea on both CD4 and CD8 T cells may also prohibit the cytokine storm by reducing COVID-19 induced immune system overactivation, thus preventing both CD8 T cell exhaustion and CD4 T cell depletion and thereby the ultimate collapse of the immune system in COVID-19 [ 189 , 190 ]. Rationales for the potential benefits of hydroxyurea in patients with COVID-19 are summarized in Table 5 .…”
Section: Urgent Questions On the Role Of Treatment With Interferon-almentioning
confidence: 99%